Polarizing film composite base material, polarizing film and preparation method of polarizing film composite base material

By using stretchable substrate and composite base material containing metal dopants, nanorods are generated during the stretching process, which solves the problems of high technical difficulty, long periods, low efficiency and risks in the preparation process of existing polarizers, and achieves the effect of simplifying the process, improving efficiency and improving reliability.

CN119882102APending Publication Date: 2025-04-25YANGTZE OPTICAL FIBRE & CABLE CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411963483.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing polarizer preparation process is difficult, has a long preparation cycle, low preparation efficiency, and has risks.

Method used

A polarizer composite base material, including a stretchable substrate and a metal-containing dopant, is used to generate nanorods during the stretching process by controlling the viscosity of the substrate and the state of the metal material, thereby preparing a polarizer.

Benefits of technology

The preparation process is simplified, the technical difficulty is reduced, the preparation cycle is shortened, the preparation efficiency is improved, and the risk of hydrogen participating in the reaction under high temperature and high pressure is avoided, which improves the long-term reliability of the polarizer.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119882102A_ABST
    Figure CN119882102A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of optical communication devices, and particularly discloses a polaroid composite base material, a polaroid and a preparation method of the polaroid composite base material. The metal-containing dopant is dispersed and distributed in the base material; the metal-containing dopant comprises at least one of a metal rod, a metal-containing composite rod, a metal ball or a metal particle; the metal-containing composite rod comprises a sub-metal rod; the base material is a stretchable material, and the material selection of the base material and the metal-containing dopant meets the following condition: when the viscosity of the base material is in a viscosity range in which the base material can be stretched, the metal material in the metal-containing dopant is in a semi-molten or molten state. According to the invention, the preparation controllability, stability and safety of the polaroid are improved, the preparation period is shortened, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of optical communication devices, and more specifically, relates to a polarizer composite mother material, a polarizer and a preparation method thereof. Background Art

[0002] Traditional polarizers are generally polarizing prisms represented by Glan-Thompson and Glan-Taylor, which are made by using the birefringence of crystals (such as calcite). Such polarizers have the advantages of high extinction ratio and transmittance, but they are expensive, bulky, and have limited resistance to light damage due to the use of adhesives. Polarizing beam splitters (PBS) are made by satisfying Brewster's law. Polarizing beam splitters are also expensive and sensitive to the angle of incident light. Two ZK3 flat glass sheets sandwiching sodium nitrate crystals form a polarizer, which can use the scattering principle to produce linear polarization, but the stability of this structure is poor. The extinction ratio of metal wire grid polarizers is limited, and resin polarizers made of polyvinyl alcohol (PVA) are not resistant to high temperatures.

[0003] Until the 1990s, Corning produced a polarizing film product with high extinction ratio, high transmittance, high acceptance angle and high weather resistance. The polarizing film was prepared by stretching reduction method. To date, the stretching reduction method has been the mainstream preparation method for preparing polarizing films for free space isolators of optical communication devices. It mainly consists of five preparation processes, namely glass melting, glass heat treatment, glass stretching, glass processing and glass reduction. There are many preparation processes, and the preparation process is cumbersome and difficult. Take the two processes of glass melting and stretching as an example. In the melting process, metal particles such as silver and copper are mainly added to the glass matrix. Taking silver as an example, silver halide (AgCl, AgBr, etc.) is usually added to the glass. The glass matrix generally selects weak phase separation borosilicate glass to facilitate the precipitation of silver halide particles. Excessive addition of silver halide will cause glass devitrification and reduce transmittance. Too little addition of silver halide will reduce the extinction ratio performance of the polarizing film. Therefore, it is necessary to reasonably control the amount of silver added. At the same time, silver has the ability to develop colors in ions, which places high demands on the quality of phase-separated glass. Stretching, as a key process for regulating the organizational structure - stretching a sphere into a rod / needle shape, directly affects the working band corresponding to the extinction ratio of the product and the angle deviation of the polarization axis. Therefore, its stretching tension, temperature / viscosity and other parameters need to be strictly controlled, and high-performance products can be stably prepared in a narrow parameter range. Looking at the entire preparation process of the stretching reduction method, there are high technical difficulties, long preparation cycles, low preparation efficiency, and hydrogen participates in the reduction reaction under high temperature and high pressure, which poses certain risks. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present application is to provide a polarizer composite mother material, a polarizer and a preparation method thereof, aiming to solve the problems of high technical difficulty, long preparation cycle, low preparation efficiency and risks in the existing polarizer preparation process.

[0005] To achieve the above-mentioned object, in a first aspect, the present application provides a polarizer composite mother material, comprising: a substrate and a metal-containing dopant; The metal-containing dopant is dispersed in the substrate; the metal-containing dopant includes at least one of a metal rod, a metal-containing composite rod, a metal ball or a metal particle; the metal-containing composite rod includes a sub-metal rod; The substrate is a stretchable material, and the materials of the substrate and the metal dopant are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range in which it can be stretched, the metal material in the metal dopant is in a semi-molten or molten state.

[0006] It can be understood that when the viscosity of the substrate is in the viscosity range where it can be stretched, if the metal dopant is in a semi-molten or molten state, the substrate will deform when the substrate is stretched; at the same time, the deformation of the substrate exerts an extrusion effect on the metal dopant, and under this effect, the metal dopant in the semi-molten or molten state deforms accordingly, and the corresponding nanorods can be generated. Therefore, the present application can prepare polarizers based on the above-mentioned polarizer composite mother material. Compared with the existing stretching and reduction method of doping metal halides, first stretching and then reducing, the present application directly stretches the composite mother material to obtain a polarization structure without the need for a reduction reaction; the technical difficulty is low, the preparation cycle is short, the preparation efficiency is high, and the direct use of metal dopants avoids the participation of hydrogen in the reaction under high temperature and high pressure, which greatly avoids the risks in the preparation process.

[0007] Furthermore, in the existing stretching-reduction method, a reduction reaction is carried out after stretching, and the volume of the structure will shrink after reduction. The stretched structure will have microscopic holes, causing uncertainty in the control of the performance of the polarizer, which may affect the long-term reliability of the polarizer. However, after stretching in the present application, there is no need to carry out a reduction reaction at a later stage, and the internal morphology of the stretched structure will not be further changed, which can greatly improve the long-term reliability of the preparation and use of the polarizer.

[0008] In one example, the weight proportion of the metal material in the metal-containing dopant in the composite base material is less than 20%, preferably 0.05% to 10%.

[0009] It should be noted that the weight ratio of the metal material in the composite matrix determines the extinction ratio performance of the polarizer and affects the transmittance performance. When the weight ratio is too small, it is difficult to prepare a polarizer with a high extinction ratio ≥50dB. For a small working bandwidth polarizer (center value ±20nm), the metal ratio in the composite matrix is ​​preferably ≥0.05%. Different working bands require different ranges of aspect ratio metal nanorods. If the weight ratio is too small, it is difficult to prepare a polarizer with a large working bandwidth (compared with the aforementioned small working bandwidth). For a polarizer with a large working bandwidth, the metal ratio in the composite matrix is ​​preferably ≥0.2%. When the weight ratio is too large, considering the scattering and absorption of light by metal, it will affect the transmittance performance of the polarizer. Therefore, the weight ratio of the metal material in the metal dopant in the composite matrix is ​​less than 20%. Preferably ≤10%; therefore, a polarizer with excellent comprehensive performance such as high extinction ratio and high transmittance is prepared, and the weight ratio of the metal material in its composite matrix can preferably be in the range of 0.05%~10%.

[0010] In one example, the diameter of the metal rod ranges from A to 10 -5 mm~A 10 -1 mm; preferably, the diameter range of the metal rod is A 10 -3 mm~A 10 -2 mm, A is the value of the thickness or diameter of the substrate, and the unit of the value is mm; The diameter range of the sub-metal rod is A 10 -4 mm~A 10 1 mm; preferably, the diameter range of the sub-metal rod is A 10 -2 mm~A 10 -1 mm; The metal ball is a nano metal ball; preferably, the diameter of the nano metal ball ranges from 5 nm to 500 nm; The metal particles are nano metal particles.

[0011] It should be noted that the diameters of the metal rods and sub-metal rods, as well as the sizes of the metal balls and metal particles, all determine the size and / or aspect ratio of the metal material to be stretched into nanorods. By limiting the corresponding size, it is expected that the corresponding polarizer can be finally obtained by stretching.

[0012] In one example, the aspect ratio of the metal rod is greater than or equal to 1.5; preferably, the aspect ratio ranges from 2 to 100; The aspect ratio of the sub-metal rod is greater than or equal to 1.5; preferably, the aspect ratio ranges from 2 to 100.

[0013] Further preferably, the metal rods and sub-metal rods in the present application can be selected with different aspect ratios, and the metal rods or sub-metal rods with different aspect ratios combined with stretching control in the composite mother material will produce nanorods with different aspect ratios; and the working bandwidth of the polarizer depends on the aspect ratio of the nanorods therein, so the composite mother material provided by the present application can be used to control the aspect ratio of the metal rods or sub-metal rods to help broaden and regulate the working bandwidth of the polarizer.

[0014] In one example, the metal balls are dispersed on the substrate in the form of single metal balls and / or metal ball assemblies; The metal particles are dispersed in the substrate in the form of a single metal particle and / or a combination of multiple metal particles.

[0015] It is understandable that by adjusting the size of the metal sphere or metal particle assembly, nanorods with different aspect ratios can be obtained.

[0016] In one example, a plurality of through holes are disposed in the substrate, and at least one metal-containing dopant is placed in one of the through holes.

[0017] Considering the difficulty of inserting metal-containing dopants into the substrate, at least one metal-containing dopant can be inserted into one through hole. When the metal-containing dopant is a metal rod or a metal-containing composite rod, the metal rod or the metal-containing composite rod can be inserted into one through hole in whole or in sections.

[0018] In one example, the sizes of the metal-containing inclusions in the substrate are the same or different.

[0019] Further preferably, considering the working band of the polarizer, if its working band is wide, the polarizer needs to have nanorods with a wide range of different length-to-diameter ratios; as the length-to-diameter ratio increases, the working band moves toward higher wavelengths. Based on the above requirements, the sizes of the metal dopants can be designed to be the same or different.

[0020] In one example, the metal-containing composite rod comprises: at least one group of composite structures nested in each other; each group of composite structures comprises a plurality of sub-metal rods and a preset substrate wrapping the sub-metal rods; preferably, a core rod is arranged in the middle of the innermost composite structure; the material of the preset substrate and the core rod is the same as that of the substrate; further preferably, the material of the substrate is glass; or, the metal-containing composite rod comprises: a core rod and a plurality of sub-metal rods embedded in the core rod, the material of the core rod is the same as that of the substrate; further preferably, the material of the substrate is glass; and / or the mass proportion of the sub-metal rod in the metal-containing composite rod is less than 50%; And / or the softening point range of the substrate is 600°C to 1500°C.

[0021] It should be noted that when the metal-containing composite rod is composed of a sub-metal rod, a core rod and a preset substrate wrapping the sub-metal rod, when the diameter of the metal-containing composite rod is equivalent to that of the metal rod, the diameter of the sub-metal rod inside it is smaller than that of the metal rod, and it is easier to stretch; when using a metal-containing composite rod, the sub-metal rods inside it are thinner, and when the composite mother material is stretched into a polarization structure, the thinner sub-metal rods will be easier to stretch into nanorods, and it will be easier to prepare a polarizer.

[0022] If the mass proportion of the sub-metal rod in the above-mentioned metal-containing dopant is too large, the above-mentioned metal-containing dopant is not suitable for being stretched alone; the mass proportion of the sub-metal rod is controlled within an appropriate range so that the metal-containing dopant can be stretched to a suitable size before being placed in the substrate and then placed in the substrate.

[0023] It is understandable that the softening point of the substrate needs to adapt to the semi-melting or melting point of the metal dopant so that the composite mother material composed of the two can be stretched to obtain a polarization structure; since the semi-melting or melting temperatures of metal materials are relatively high, a substrate with a relatively high softening point needs to be selected in this application to match it.

[0024] In a second aspect, the present application provides a polarizer, which is obtained by stretching the composite base material described in the first aspect or any one of the examples of the first aspect; when the composite base material is stretched, when the viscosity of the substrate is in the viscosity range in which it can be stretched, the metal material in the metal-containing dopant is in a semi-molten or molten state.

[0025] In a third aspect, the present application provides a stretching method for a polarizer as described in the second aspect, wherein when the composite base material is stretched, the viscosity of the base material is controlled within a range of 10 2 mooring~10 13 Poise, preferably the substrate viscosity is 10 4 mooring~10 10 The stretching is carried out within the range of 10 MPa to 300 MPa, and the discharge speed is controlled within the range of 10 mm / min to 1000 mm / min.

[0026] It should be noted that, due to the increase in the softening point range of the stretched substrate from 600°C to 1500°C, the corresponding viscosity range of the stretched substrate is 10 2 mooring~10 13In addition, tensile tension is a key parameter indicator for tissue structure regulation. The applied tension range is 10MPa~300MPa. Within this range, the size of the pulling force is adjusted according to the size of the stretched material. As the tension increases, the aspect ratio increases. Because metal materials tend to spheroidize under the action of specific surface tension, the aspect ratio shrinks. At this time, a high discharge speed can reduce the shrinkage. Therefore, it is preferred that the discharge speed is greater than 10mm / min, but the stability of the stretching is poor if the discharge speed is too fast. Considering the stability, the discharge speed should not exceed 1000mm / min.

[0027] In a fourth aspect, the present application provides a method for preparing the polarizer composite mother material described in the first aspect or any example of the first aspect, comprising: Providing a substrate; Providing a metal-containing dopant; the metal-containing dopant comprises at least one of a metal rod, a metal-containing composite rod, a metal ball or a metal particle; the metal-containing composite rod comprises a sub-metal rod; The metal dopant is placed in a substrate to obtain a composite mother material; the substrate is a stretchable material, and the materials of the substrate and the metal dopant are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range in which it can be stretched, the metal material in the metal dopant is in a semi-molten or molten state.

[0028] In one example, when the metal-containing dopant is a metal rod or a metal-containing composite rod, the insertion is inserted by punching; preferably, the metal-containing composite rod is inserted into the substrate by punching after being stretched; When the metal dopant is a metal ball or metal particle, the implantation is performed by implantation; when the implantation is performed by ion beam implantation, the target material is at least one of silver, gold, copper and other metals, and the implantation is performed on both sides in the whole surface or in a regional selective manner, the implantation energy is greater than or equal to 10 MeV, and the gas pressure range during the implantation is 0.01 Pa~1 Pa; preferably, the implantation area range of the regional selective implantation is 0.01 mm 2 ~10mm 2 The injection area interval range is 0.01Amm~5Amm, A is the numerical value of the thickness or diameter of the substrate, and the unit of the numerical value is mm; further preferably, when the injection method is ion beam injection, the thickness or diameter of the substrate is preferably 0.01mm~5mm.

[0029] It should be noted that when the metal-containing composite rod is stretched and then inserted, the number of stretching times required to prepare the polarizer using the metal-containing composite rod is greater than the number of stretching times of the composite mother material using the metal rod. Therefore, the range of the aspect ratio of the sub-metal rod used in the metal-containing composite rod can be wider than the range of the aspect ratio of the metal rod in the aforementioned embodiment, and it is easier to prepare the polarizer.

[0030] In one example, when the placing is carried out by punching, holes are punched inside the substrate along the stretching direction of the substrate.

[0031] Further preferably, when the direction of the through holes is consistent with the direction in which the substrate is stretched, the metal dopant is more easily stretched into nanorods, which can improve the control accuracy of the light transmission axis of the polarizer (ie, the long axis of the nanorods).

[0032] In general, the above technical solutions conceived by this application have the following beneficial effects compared with the prior art: The present application provides a polarizer composite mother material, a polarizer and a preparation method thereof. When the viscosity of the substrate is in the viscosity range in which it can be stretched, if the metal dopant is in a semi-molten or molten state, the substrate will be deformed when the substrate is stretched. At the same time, the deformation of the substrate produces an extrusion effect on the metal dopant, and the metal dopant in the semi-molten or molten state will be deformed accordingly under this effect. Therefore, the present application can prepare a polarizer based on the above-mentioned polarizer composite mother material. Compared with the existing stretching and reduction method of doping metal halides, which is first stretched and then reduced, the present application directly stretches the composite mother material to obtain a polarization structure without the need for a reduction reaction. The technical difficulty is low, the preparation cycle is short, and the preparation efficiency is high. The direct use of metal dopants avoids the participation of hydrogen in the reaction under high temperature and high pressure, which greatly avoids the risks in the preparation process.

[0033] The present application provides a polarizer composite mother material, a polarizer and a preparation method thereof. In the existing stretching reduction method, a reduction reaction is performed after stretching, and the volume of the structure will be reduced after reduction, and the stretched structure will have microscopic holes, which will cause uncertainty in the control of the polarizer performance and may affect the long-term reliability of the polarizer. However, the present application does not require a reduction reaction after stretching, and will not further change the internal morphology of the stretched structure, which can greatly improve the long-term reliability of the preparation and use of the polarizer. While meeting the product performance, the present application optimizes the preparation and stretching of the mother material, reduces the three processes of melting, crystallization and reduction, increases the safety of the entire polarizer preparation, improves the preparation efficiency, and reduces energy consumption.

[0034] The present application provides a polarizer composite mother material, a polarizer and a preparation method thereof, wherein the aspect ratio of the metal rods and the metal-containing composite rods in the metal-containing dopant can be selected, and the size of the metal balls and the metal particles can be adjusted, so the working bandwidth of the polarizer after stretching can be regulated based on the regulation of the size of the metal-containing dopant; compared with the more random change of the aspect ratio in the existing stretching-reduction method, the working bandwidth of the polarizer in the present application is more adjustable.

[0035] The present application provides a polarizer composite mother material, a polarizer and a preparation method thereof. When a metal-containing composite rod is used, the distribution of the sub-metal rods in the substrate will be more dispersed and uniform and the sub-metal rods will be thinner, thereby improving the uniformity of the distribution of the metal material in the polarizer, and the performance of the corresponding polarizer will be more uniform and easier to prepare into nanorods, so the controllability is higher. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] FIG. 1( a ) is a first structural diagram of a polarizer composite matrix provided in an embodiment of the present application; FIG. 1( b ) is a second structural diagram of a polarizer composite mother material provided in an embodiment of the present application; FIG. 1( c ) is a third structural diagram of the polarizer composite mother material provided in an embodiment of the present application; FIG. 1( d ) is a fourth structural diagram of a polarizer composite mother material provided in an embodiment of the present application; FIG. 1( e ) is a fifth structural diagram of a polarizer composite base material provided in an embodiment of the present application; Figure 2 This is a flow chart of the first method for preparing the polarizer composite mother material provided in the embodiment of the present application; FIG3( a ) is a cross-sectional structural diagram of a metal composite rod contained in a composite matrix of a polarizer provided in an embodiment of the present application; FIG3( b ) is a first cross-sectional schematic diagram of a metal composite rod contained in a polarizer composite matrix provided in an embodiment of the present application; FIG3( c ) is a second cross-sectional schematic diagram of a metal composite rod contained in a polarizer composite matrix provided in an embodiment of the present application; FIG3( d ) is a third cross-sectional schematic diagram of a metal composite rod contained in a polarizer composite matrix provided in an embodiment of the present application; FIG3( e ) is a fourth cross-sectional schematic diagram of a metal composite rod contained in a polarizer composite matrix provided in an embodiment of the present application; FIG3( f ) is a fifth cross-sectional schematic diagram of a polarizer composite matrix containing a metal composite rod provided in an embodiment of the present application; Figure 4 This is a flow chart of a second method for preparing a polarizer composite mother material provided in an embodiment of the present application; FIG5( a ) is a sixth structural diagram of a polarizer composite base material provided in an embodiment of the present application; FIG5( b ) is a seventh structural diagram of the polarizer composite base material provided in an embodiment of the present application; Figure 6 This is a schematic diagram of the eighth structure and preparation process of the polarizer composite mother material provided in the embodiments of the present application; Figure 7 This is a flow chart of a third method for preparing a polarizer composite mother material provided in an embodiment of the present application; Figure 8 is a schematic diagram of a stretching furnace provided in an embodiment of the present application; Fig. 9 It is a schematic diagram of the microscopic morphology of the polarizer obtained by stretching provided in the embodiment of the present application.

[0037] In all the drawings, the same figure marks are used to represent the same elements or structures, wherein: 10 is a substrate, 20 is a metal rod, 21 is a core rod, 22 is a sub-metal rod, 23 is a preset substrate wrapping the sub-metal rod, 231 is a first layer of casing, 232 is a second layer of casing, 233 is a third layer of casing, 30 is a metal ball, 40 is a hole, 50 is a metal particle, 61 is the front side of the substrate, 62 is the back side of the substrate, 70 is an ion beam, 80 is a feeding area, 81 is a stretching area, 82 is a discharging area, 100 is a nanorod, and 200 is a stretched substrate. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0039] The embodiments of the present application are described below in conjunction with the drawings in the embodiments of the present application.

[0040] It should be noted that the theoretical basis for the polarization effect of polarizers is mainly the interaction between the metal nanoparticles in the glass matrix and the electric vector of the light wave, which produces the collective resonance absorption of a large number of free electrons in the metal particles. When the electric vector direction of the incident light wave is parallel to the long axis direction of the rod-shaped metal particle, this part of the incident light will be absorbed by the oscillation of free electrons inside the metal particle, converting the light energy into heat energy; and when the electric vector direction of the incident light wave is perpendicular to the long axis direction of the rod-shaped metal particle, this part of the light will be transmitted. Finally, the incident natural light will be converted into linearly polarized light after passing through the polarizing glass.

[0041] Furthermore, the polarization effect of the polarizer is closely related to the shape and size of the nanoparticles. The controllability of the metal particles in the regularly arranged nanoparticle array plays a decisive role in the polarization performance of the polarized glass.

[0042] The main purpose of the embodiments of the present application is to provide a polarizer composite mother material to prepare a polarizer based on the composite mother material; on this basis, a new polarizer preparation method is provided to simplify the preparation process, shorten the preparation cycle, improve production efficiency, reduce preparation energy consumption, and at the same time increase the controllability and stability of polarizer preparation.

[0043] Specifically, the polarizer composite mother material provided in the embodiment of the present application includes: a substrate and a metal-containing dopant; the metal-containing dopant is dispersed in the substrate; the metal-containing dopant includes a metal rod (see Figure 1(a) to Figure 1(e) ), metal-containing composite rods (see Figure 3(a) to Figure 3(f) ), metal balls (see Figure 5(a), Figure 5(b)) or metal particles (see Figure 6 ) at least one of the following.

[0044] Further preferably, the above-mentioned substrate is a stretchable material, and the materials of the substrate and the metal dopant are selected to meet the following conditions: when the viscosity of the substrate is in the viscosity range where it can be stretched, the metal in the metal dopant is in a semi-molten or molten state, so as to ensure that the microstructure of the composite base material can be regulated during stretching, thereby ensuring that the ideal aspect ratio nanorods are obtained.

[0045] Further preferably, the above-mentioned substrate is preferably a material with a light transmittance of ≥80% and a softening point in the range of 600°C to 1500°C; usually, those skilled in the art select glass that meets the above requirements as the substrate.

[0046] The solutions provided by the embodiments of the present application are introduced in detail below in combination with the first to fourth embodiments.

[0047] The first type of embodiment: Combination Figure 1(a) to Figure 1(e) It can be seen that when the metal dopant is a metal rod 20, the metal rod 20 is dispersed in the substrate 10 along a preset direction; specifically, the preset direction is that the length direction of the metal rod 20 is consistent with the stretching direction when the substrate 10 is stretched, so that the composite base material can be stretched to obtain a polarizer, and it helps to improve the control accuracy of the transmittance axis of the polarizer.

[0048] As a further example, the aspect ratio of the metal rod 20 is greater than or equal to 1.5; preferably, the aspect ratio ranges from 2 to 100. It is understood that the aspect ratio of the metal rod 20 after being stretched determines the working bandwidth of the polarizer. The stretching can be multiple stretchings, so the range of the aspect ratio before stretching can be relatively wide, and the final aspect ratio can be controlled within the working requirement range of the polarizer.

[0049] As an example, the diameter of the metal rod 20 ranges from A to 10 -5 mm~A 10 -1 mm; preferably, the diameter range of the metal rod 20 is A 10 -3 mm~A 10 -2 mm, A is the thickness or diameter of the substrate 10, and the unit of the above values ​​is mm.

[0050] It is understandable that the substrate 10 may be a block (e.g. Figure 1(a) to Figure 1(d) ) or cylindrical rod shape (as shown in Figure 1(e)).

[0051] As a further example, the sizes of the metal rods 20 are the same (as shown in Figures 1(a), 1(b) and 1(e)) or not exactly the same (as shown in Figures 1(c) and 1(d)); the metal rod 20 is a whole metal rod or (as shown in Figures 1(a) and 1(e)) a combination of multiple segmented sub-metal rods (as shown in Figures 1(b), 1(c) and 1(d)). It can be understood that the size of the metal rod 20 determines the working bandwidth, and the number of directional arrangements in the same direction determines the value of the extinction ratio. When the sizes of the metal rods 20 are the same, the working bandwidth of the polarizer is narrower, and when the sizes of the metal rods 20 are not exactly the same, the working bandwidth of the polarizer is wider. Those skilled in the art can design the size and number of the metal rods 20 according to actual needs to ultimately obtain a polarizer with corresponding performance.

[0052] It should be further explained that the scattering of light by the metal in the substrate will lead to a decrease in transmittance. Considering the overall transmittance of the material, the proportion of the metal rod (when the metal rod is thin, it can be called a metal wire) in the parent material does not exceed 20% Wt, preferably less than 10% Wt. Since the metal element is added to the substrate, compared with metal halides, there is no need to consider the reduction depth, so the content of the metal wire / rod in the substrate can be lower than the metal content in the conventional stretch reduction method to melt the metal halide-containing substrate.

[0053] The preparation method of the above polarizer composite base material can be found in Figure 2 As shown, the following steps are included: Step S101, providing a substrate; the substrate is a stretchable material, and its light transmittance is greater than a preset light transmittance; In some embodiments, the material of the substrate can be conventional glass, and the glass system is not limited, and can be borosilicate glass, soda-lime glass, aluminosilicate glass, etc. High softening point glass and high transmittance glass are preferred, with a softening point Tg of 600°C to 1500°C and a transmittance T≥80%. The metal wire / rod can be gold, silver, copper or other metals, preferably silver and copper, and is selected in combination with the softening point and transmittance of the glass substrate and the melting point of the metal rod material.

[0054] Step S102, providing a plurality of metal rods; the materials of the metal rods and the substrate are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range in which it can be stretched, the metal rods are in a semi-molten or molten state; Considering the overall uniformity, the metal wires / rods need to be evenly dispersed in the glass matrix. It can be further understood that the distance of the metal rods along the short diameter direction can be determined by the relevant extinction ratio requirements, the weight ratio of the metal rods, the material of the metal rods, and the design of the composite base material. It should be noted that when the polarizer is expected to have a relatively high extinction ratio, it can be achieved by controlling the distance between adjacent metal rods. The smaller the distance between the above metal rods, the lower the extinction ratio. The distance between the metal rods is preferably: <A / 2mm, A represents the thickness of the base material A mm. At the same time, the metal rods are arranged along the same direction (stretching direction) and pre-oriented along the stretching direction. This method has a pre-oriented effect. Since they are arranged along the same direction during stretching, that is, the stretching direction, it helps to improve the control accuracy of the polarizer's light transmission axis.

[0055] Step S103, opening a plurality of dispersed through holes in the substrate; Preferably, the above-mentioned method of opening the through hole includes but is not limited to: drilling, acid etching, chemical reaction or dissolution.

[0056] Step S105 , placing the plurality of metal rods into corresponding through holes to obtain a polarizer composite mother material.

[0057] It should be noted that assembling the metal rods in the glass substrate by nesting is not limited to mechanical connection such as drilling, acid etching holes and then inserting the rods to obtain the polarizer composite mother material, which is a relatively simple combination method. It can also be combined by chemical reaction or dissolution, which is more difficult because the glass substrate and the metal rods are two types of materials.

[0058] Specifically, the size of the metal rod and the composite mother material can be matched and adjusted according to actual needs and conditions. The width or outer diameter of the composite mother material can be adjusted according to the stretching equipment. Considering the single-time preparation efficiency, for the block composite mother material, the width is preferably greater than 180 mm, and for the cylindrical rod-shaped mother material, the outer diameter is preferably > 150 mm. The length of the mother material is adjusted according to the size of the stretching tower. In theory, the longer the single-time preparation efficiency is higher. In addition, the thickness of the mother material is limited. If the mother material thickness is Amm, A is preferably ≤20mm. The current free-space optical isolator is generally 0.2 mm. Considering the processing loss, it is generally stretched to much greater than 0.2 mm. From the original mother material thickness, metal rods of different outer diameters in this range can be selected for assembly. Metal rods of different outer diameters combined with stretching control will produce metal rods with different aspect ratios, which will help to broaden the working bandwidth of the polarizer.

[0059] Since the nanorods are ultimately stretched into different aspect ratios, they can also be segmented in advance when the base material and the metal rod are assembled. They can be divided into multiple sections of the same specification (outer diameter of the metal rod / wire), and multiple sections of metal rods with different outer diameters can be selected for combination. However, it is more difficult to operate different outer diameters during assembly, so multiple sections of metal rods with the same specification are preferred, and there is no limitation on the length direction of the metal rods.

[0060] The second embodiment: In some further extended embodiments, based on the above Figure 1(a) to Figure 1(e) In the embodiment shown, the metal rod 20 can be replaced by a metal-containing composite rod, such as Figure 3(a) to Figure 3(f) As shown, the metal-containing composite rod comprises: at least one group of composite structures nested with each other; each group of composite structures comprises a plurality of sub-metal rods 22 and a preset substrate 23 wrapping the sub-metal rods 22, and a core rod 21 is arranged in the middle of the innermost composite structure, see Figure 3(a) to Figure 3(c) As shown, when the core rod 21 is not provided in the middle of the innermost composite structure, the structure can be seen as shown in FIG3(f).

[0061] The materials of the preset substrate and the core rod are the same as the above-mentioned substrate.

[0062] Further preferably, the metal-containing composite rod comprises: a core rod 21 and a plurality of sub-metal rods 22 embedded in the core rod, as shown in FIG. 3( d ) and FIG. 3( e ).

[0063] Specifically, when there are multiple groups of nested composite structures, 231 in Figure 3(c) and Figure 3(f) is a preset substrate for wrapping the sub-metal rods in the first layer of composite structure, 232 is a preset substrate for wrapping the sub-metal rods in the second layer of composite structure, and 233 is a preset substrate for wrapping the sub-metal rods in the third layer of composite structure.

[0064] It should be noted that when metal-containing composite rods are used to replace metal rods, the distribution of the sub-metal rods in the substrate will be more dispersed and uniform, and the performance of the corresponding polarizer will be more uniform.

[0065] It can be understood that the above-mentioned metal-containing composite rod can be inserted into the substrate after stretching, and the above-mentioned stretching can be one time or multiple times; because the number of stretching times of the polarizer when using the metal-containing composite rod is greater than the number of stretching times of the composite mother material using the metal rod 20, the sub-metal rod 22 used in the metal-containing composite rod has a wider range of aspect ratios than the range of aspect ratios of the metal rod 20 in the aforementioned embodiment, and subsequently, a polarizer with corresponding performance can be finally obtained by successively stretching the mother material and the composite mother material multiple times.

[0066] As a further example, when the metal-containing dopant is a metal-containing composite rod, the sub-metal rods 22 are dispersed in the metal-containing composite rod along a preset direction, and the above-mentioned preset direction is that the length direction of the sub-metal rods 22 is consistent with the stretching direction when the substrate 10 is stretched.

[0067] In one example, the diameter of the sub-metal rod 22 ranges from A to 10 -4 mm~A 10 1 mm; preferably, the diameter range of the sub-metal rod 22 is A 10 -2 mm~A 10 -1 mm, A is the thickness or diameter of the substrate 10, and the unit of the value is mm; and / or the weight of the sub-metal rod in the composite parent material is less than 20%; And / or the aspect ratio of the sub-metal rod is greater than or equal to 1.5; preferably, the aspect ratio ranges from 2 to 100.

[0068] It can be further understood that the distance of the sub-metal rods along the short diameter direction can be determined by the relevant extinction ratio requirements, the weight ratio of the sub-metal rods, the material of the sub-metal rods and the design of the composite parent material.

[0069] Same as above Figure 1(a) to Figure 1(e) In the illustrated embodiment, when the metal-containing dopant is a metal-containing composite rod, the sub-metal rods may have the same or different sizes; the sub-metal rod may be a whole sub-metal rod or a combination of multiple segmented sub-metal rods.

[0070] In some embodiments, considering the uniformity of the sub-metal rod in the metal-containing composite rod, it is preferred to adopt a multi-level nested assembly. The outer diameter of the core rod is not less than the size of the metal rod, and the wall thickness of the sleeve is not less than the size of the sub-metal rod. Without considering the complexity of the operation, the metal-containing composite rod can be stretched after assembly, and the stretched metal-containing composite rod can replace the above Figure 1(a) to Figure 1(e) The metal rods in the glass are assembled and repeated to improve the uniformity of the metal distribution in the glass matrix.

[0071] It should be noted that the metal rods in the polarizer are usually required to be nanorods of nanometer scale (nanometer refers to the size of the metal rod, such as diameter and / or length, etc.). When a metal-containing composite rod is used, the sub-metal rod 22 will obviously be thinner than the metal rod 20. When the composite mother material is stretched into a polarization structure, the sub-metal rod 22 will be more easily stretched into a nano-metal rod. Therefore, the above solution has certain advantages.

[0072] The preparation method of the above polarizer composite base material can be found in Figure 4 As shown, the following steps are included: Step S201, providing a substrate; the substrate is a stretchable material, and its light transmittance is greater than a preset light transmittance; Step S202, providing a plurality of metal-containing composite rods; the metal-containing composite rods include: at least one group of composite structures nested with each other; each group of composite structures includes a plurality of sub-metal rods and a preset substrate wrapping the sub-metal rods; preferably, a core rod is provided in the middle of the innermost composite structure; the material of the preset substrate and the core rod is the same as that of the substrate; further preferably, the material of the substrate is glass; or, the metal-containing composite rods include: a core rod and a plurality of sub-metal rods embedded in the core rod, the material of the core rod is the same as that of the substrate; further preferably, the material of the substrate is glass; The mass proportion of the sub-metal rod in the metal-containing composite rod is less than 50%; It should be noted that when the metal-containing composite rod is composed of a sub-metal rod, a core rod and a preset substrate wrapping the sub-metal rod, when the diameter of the metal-containing composite rod is equivalent to that of the metal rod, the diameter of the sub-metal rod inside it is smaller than that of the metal rod, and it is easier to stretch; when using a metal-containing composite rod, the sub-metal rods inside it are thinner, and when the composite mother material is stretched into a polarization structure, the thinner sub-metal rods will be easier to stretch into nanorods, and it will be easier to prepare a polarizer.

[0073] If the mass proportion of the sub-metal rod in the above-mentioned metal-containing dopant is too large, the above-mentioned metal-containing dopant is not suitable for being stretched alone; the mass proportion of the sub-metal rod is controlled within an appropriate range so that the metal-containing dopant can be stretched to an appropriate size before being placed in the substrate; when the metal-containing composite rod is placed after being stretched, the number of stretching times required for preparing the polarizer using the metal-containing composite rod is greater than the number of stretching times of the composite mother material using the metal rod. Therefore, the range of the aspect ratio of the sub-metal rod used in the metal-containing composite rod can be wider than the range of the aspect ratio of the metal rod in the aforementioned embodiment, and it is easier to prepare the polarizer.

[0074] Step S203, opening a plurality of dispersed through holes in the substrate; Step S204, placing the plurality of metal-containing composite rods into corresponding through holes to obtain a polarizer composite mother material.

[0075] The third embodiment: 5(a) and 5(b), when the metal dopant is a metal ball 30, the metal ball may be a nano metal ball; preferably, the diameter of the metal ball is in the range of 5 nm to 500 nm; and / or the metal ball is a solid ball or a hollow ball; and / or the sizes of the metal balls are the same (as shown in FIG. 5(a)) or not exactly the same (as shown in FIG. 5(b)); and / or the metal balls are dispersed in the pores 40 of the substrate in the form of a single metal ball and / or a nano metal ball assembly.

[0076] In one embodiment, the preparation method of the composite matrix can be as follows: The substrate and the metal balls are combined through an intermediate material. For example, porous glass (macropores can be holes with a diameter of more than 100 nm) can be prepared by sol-gel, adding pore-forming agents, organic foams, foaming methods, etc., and then the metal powder is dissolved in an organic solvent, and the porous structured glass is immersed in an organic solvent containing the metal powder, and then the temperature is increased and dried to volatilize the organic solvent, and finally the composite mother material containing the metal dopant as the metal ball is obtained.

[0077] It should be noted that the above preparation method is a relatively conventional method, and those skilled in the art may also choose other methods for preparation according to actual conditions and technical levels, and the embodiments of the present application do not impose any limitation on this.

[0078] It is understandable that, in order to reduce the ratio of stretching and scaling, nano metal balls can be incorporated into the above-mentioned substrate, preferably metal materials such as silver, gold, and copper. The scattering of light by metal in the glass matrix will lead to a decrease in transmittance. Considering the overall transmittance of the material, the weight of the metal balls in the parent material does not exceed 20% Wt, and more preferably does not exceed 10% Wt. Considering the overall transmittance of the material, the particle size of the nanospheres cannot be too large, preferably ≤500nm nano metal balls, because there is a thermal process in the stretching stage that will be accompanied by the growth of particles, more preferably ≤100nm spherical particles. Considering the overall uniformity, the metal balls need to be evenly dispersed in the glass matrix. Among them, the metal nano ball powder is filled in the reserved space. In order to extend the bandwidth, within the range of spherical particles preferably ≤100nm, nano balls of different particle sizes within the range of particle size can be selected for combination and addition. When filling, the whole can be filled, or part of the nano ball powder can be filled at a certain interval, and the gap can be filled with a glass substrate. The same parent material length and width are adjusted according to the stretching equipment, regardless of the length and width of the parent material. The thickness of the base material is limited, preferably the base material thickness is ≤20mm.

[0079] The fourth embodiment: See attached Figure 6 When the metal dopant is metal particles 50, the metal particles 50 are nano-metal particles; and / or nano-metal spheres are dispersed in the substrate in the form of a single nano-metal particle and / or a combination of multiple nano-metal particles.

[0080] It should be noted that this scheme is mainly through the direct doping of metal into the substrate, and the appropriate uniform doping is the difficulty of regulation. First, the doping can be achieved by ion beam sputtering deposition and high-energy ion beam 70 injection. Among them, ion beam sputtering provides target material clusters, and the high-energy ion beam injects the sputtered metal cluster material into the glass matrix. Considering the limited depth of ion beam injection, ion beam injection can be performed on the front side 61 and the back side 62 of the substrate respectively.

[0081] The preparation method of the above polarizer composite base material can be found in Figure 7 As shown, the following steps are included: Step S301, providing a substrate; the substrate is a stretchable material, and its light transmittance is greater than a preset light transmittance; Step S302, providing a metal target; the materials of the metal target and the substrate are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range in which it can be stretched, the metal material corresponding to the metal target is in a semi-molten or molten state; Step S303, injecting metal particles in the metal target material into the substrate by ion beam sputtering deposition and ion beam implantation to obtain a polarizer composite mother material.

[0082] Preferably, limited by the injection effect, the mother glass may be thinner glass, and its thickness is preferably in the range of 0.01mm~5mm. Specifically, the energy of the high-energy particle beam is preferably ≥10MeV. Taking into account the uniformity of the entire glass, a large-sized high-energy particle source is preferred. Metal particles such as silver / gold / copper are provided by high-purity target materials. Under a negative pressure environment of 0.01Pa~1Pa, the target material is impacted by an ion beam to peel off the target clusters. The target clusters are injected into the glass matrix under the impact of the high-energy ion beam. The whole surface can be injected, or selective injection can be performed by shielding with a photomask. When shielded by a photomask, the injection area can be within 0.01mm 2 ~10mm 2 The injection area interval can be controlled between 0.01Amm and 5Amm, where A represents the thickness of the base glass A mm. After single-sided injection, the target is injected on the other side, and the preferred target material is silver / gold / copper.

[0083] It can be understood that, based on the composite mother materials provided in the first to fourth embodiments, the corresponding polarization structures can be obtained by stretching them; and then the polarization structures can be simply post-processed to obtain the polarizers.

[0084] Preferably, in combination with the above embodiments, after the polarizer composite mother material provided in the above embodiments is stretched, the composite mother material can be obtained to obtain the relevant polarization structure. The above composite mother material is stretched to regulate the internal organizational structure, and at the same time, the material size is adjusted to be close to the product size (mainly thickness direction regulation, the wider the width, the larger the size of the prepared material, and the higher the utilization rate). The stretching equipment is mainly composed of a stretching tower, a stretching furnace, a feeding unit, a discharging unit, and a size detection unit. Among them, the stretching tower mainly plays the role of supporting the overall structure and reserving space for stretching operations. It is preferably extended longitudinally along the direction of gravity so that the stretching direction is consistent with the gravity direction.

[0085] More preferably, if Figure 8 As shown, the stretching furnace can be divided into three areas according to the temperature field distribution: feeding area 80, stretching area 81 and discharging area 82. The overall temperature distribution shows that the temperature in stretching area 81 is the highest, and the temperatures at both ends are relatively low. Each area has a separate temperature increase / decrease and temperature measurement control system. The stretching furnace control system and the feeding unit and discharging unit control systems are unified into a control cabinet and are uniformly controlled by a controller. The feeding unit is mainly responsible for providing raw materials from the rod / sheet glass mother material to the inside of the furnace along the stretching direction, regulating the product size, and preventing the stretching from being too thin and broken. The discharging unit is mainly responsible for pulling the products of the required specifications out of the stretching high temperature zone, while ensuring that the nanorods are directional stretched in the same direction. Stretching has strict requirements on temperature viscosity, and the temperature control accuracy is within ±3°C, the lower the better.

[0086] It should be noted that, due to the increase in the softening point range of the stretched substrate from 600°C to 1500°C, the corresponding viscosity range of the stretched substrate is 10 2 mooring~10 13 In addition, tensile tension is a key parameter indicator for tissue structure regulation. The applied tension range is 10MPa~300MPa. Within this range, the size of the pulling force is adjusted according to the size of the stretched material. As the tension increases, the aspect ratio increases. Because metal materials tend to spheroidize under the action of specific surface tension, the aspect ratio shrinks. At this time, a high discharge speed can reduce the shrinkage. Therefore, it is preferred that the discharge speed is greater than 10mm / min, but the stability of the stretching is poor if the discharge speed is too fast. Considering the stability, the discharge speed should not exceed 1000mm / min.

[0087] For the first embodiment, the stretching test is carried out in a certain temperature / viscosity range, wherein the viscosity range of the stretching zone is preferably: 10 4 mooring~10 13It is preferred that the metal rod is stretched in a semi-molten state, and the stretching direction is preferably vertically downward along the direction of gravity. In order to improve the product quality, inert gas protection (nitrogen, argon, etc.) is passed through the furnace during stretching. By adjusting the stretching parameters, the tension is greater than 10MPa, and the inlet and outlet / material speed is matched and set according to the discharge size. During stretching, the metal rod in the substrate is gradually stretched thinner under the action of tension. As the scale increases, the composite mother material is thinned. Under the extrusion effect of the deformation of the substrate on the metal rod, the metal rod / wire is broken and divided into multiple sections. At the same time, the metal rod / wire is pulled to the nanoscale, and finally a nanorod is formed. Several sections of nanorods are in the same straight line (vertically downward in the direction of gravity). The aspect ratio refers to the ratio of the long end L and the short end W of the nanorod formed by stretching. Different aspect ratios correspond to different working bands. From the visible light band to the communication band, the aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1~20, and for the visible light band, it is more preferably in the range of 1~3.

[0088] In one example, the microscopic morphology after stretching is shown in FIG. Fig. 9 As shown, 100 is the nanorod and 200 is the stretched substrate. The stretched product is already a semi-finished product and can be sold after post-processing.

[0089] Specifically, in some embodiments, the post-processing of the above-mentioned products may include: processing and coating post-processing of the stretched samples. The processing is mainly to cut the required size by a dicing machine, and to control the flatness, parallelism, and other surface qualities by a grinding and polishing machine. The processing and grinding and polishing processes are interchangeable, and generally processing is performed first and then grinding and polishing. After processing, it is the finished product. Since this step is relatively mature, it will not be described in detail. Similarly, coating is mainly used to improve the transmittance of the product. For products like optical isolators, the insertion loss of the overall device needs to be considered. Therefore, the raw materials of the isolator, the polarizer and the Faraday plate, need to be coated. Since the refractive index of the glue is close to that of the polarizer, the polarizer only needs to be coated on one side to the air. The coating step is relatively mature and will not be described in detail.

[0090] For the second type of embodiment, For the second embodiment, the stretching test is carried out in a certain temperature / viscosity range, similar to the first embodiment, wherein the viscosity range of the stretching zone is preferably: 10 4 mooring~10 13The metal rod is preferably stretched in a semi-molten state, and the stretching direction is preferably vertically downward along the direction of gravity. In order to improve the product quality, inert gas protection (nitrogen, argon, etc.) is passed through the furnace during stretching. By adjusting the stretching parameters, the tension is greater than 10MPa, and the inlet and outlet / material speed is matched and set according to the discharge size. During stretching, the sub-metal rod in the substrate is gradually stretched thinner under the action of tension. As the scale increases, the composite mother material is thinned. Under the extrusion effect of the deformation of the substrate on the sub-metal rod, the sub-metal rod / wire is broken and divided into multiple sections. At the same time, the sub-metal rod / wire is pulled to the nanoscale, and finally a nanorod is formed. Several sections of nanorods are in the same straight line (vertically downward in the direction of gravity). The aspect ratio refers to the ratio of the long end L and the short end W of the nanorod formed by stretching. Different aspect ratios correspond to different working bands. From the visible light band to the communication band, the aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1~20, and for the visible light band, it is more preferably in the range of 1~3.

[0091] Specifically, the post-processing process of the product is the same as that of the first embodiment.

[0092] For the third embodiment, the stretching test is carried out in a certain temperature / viscosity range. Different from the first and second embodiments, the spherical nano-metal particles have a larger specific surface area. For example, the specific surface area of ​​the silver metal sphere is larger than that of the silver chloride sphere. Therefore, it has higher requirements for the stretching viscosity range and the stretching tension. The preferred viscosity range of the stretching zone is: 10 4 mooring~10 11 It is preferred that the metal ball is stretched in a near-molten state, and the stretching direction is preferably vertically downward along the direction of gravity. In order to improve product quality, an inert gas protection (nitrogen, argon, etc.) is passed through the furnace during stretching. By regulating the stretching parameters, it is preferred that the stretching force is greater than 30MPa, and the inlet / outlet speed is matched and set according to the discharge size. During stretching, the nanospheres in the substrate are gradually stretched thinner under the action of tension, and the composite mother material is thinned. Nanorods are formed under the extrusion and tension of the metal balls caused by the deformation of the substrate. The aspect ratio refers to the ratio of the long end L and the short end W of the nanorod formed by stretching. Different aspect ratios correspond to different working bands. From the visible light band to the communication band, the aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1 to 20, and for the visible light band, it is more preferably in the range of 1 to 3.

[0093] Specifically, the post-processing process of the product is the same as that of the first embodiment.

[0094] For the fourth embodiment, a tensile test is conducted in a certain temperature / viscosity range. Since nano-metal particles are incorporated, it is similar to the third embodiment in which nano-metal balls are incorporated. The preferred viscosity range of the tensile region is: 10 4 mooring~10 11It is preferred that the metal particles are stretched in a near-molten state, and the stretching direction is preferably vertically downward along the direction of gravity. In order to improve product quality, an inert gas protection (nitrogen, argon, etc.) is passed through the furnace during stretching. By regulating the stretching parameters, it is preferred that the stretching force is greater than 30MPa, and the inlet / outlet speed is matched and set according to the discharge size. During stretching, the nano-metal particles in the substrate are gradually stretched thinner under the action of tension, and the composite parent material is thinned. Nanorods are formed under the extrusion and tension of the metal particles by the deformation of the substrate. The aspect ratio refers to the ratio of the long end L and the short end W of the nanorod formed by stretching. Different aspect ratios correspond to different working bands. From the visible light band to the communication band, the aspect ratio L / W (length / width) of the nanorod is preferably in the range of 1 to 20, and for the visible light band, it is more preferably in the range of 1 to 3.

[0095] It is further understood that, compared with the main problems existing in the existing stretching reduction method for preparing polarized glass sheets, and the advantages of the solution provided by the embodiments of the present application, they are summarized as follows: 1. The existing mainstream stretching reduction method for preparing polarizers has many preparation steps, complicated processes, high power consumption, long preparation cycle for the entire process, and low preparation efficiency. However, the present application obtains polarizers by stretching the above-mentioned new polarizer composite mother material, which has a simple process, low power consumption, short preparation cycle and high efficiency.

[0096] 2. The melting process formula components in the stretching reduction preparation method mostly use borosilicate glass, and the choice of glass matrix is ​​relatively limited. It is difficult to prepare high-quality microcrystalline glass with excellent comprehensive properties such as high transmittance and high uniformity, and it is difficult to control the introduction ratio of microcrystalline and particle size; in this application, the substrate only needs to select a material with high light transmittance and a softening point that matches the semi-melting point or melting point of the metal to prepare a polarizer. The choice of substrate is wider, and there is no need for reduction reaction. The aspect ratio of the corresponding nanorod only needs to control the size of the metal dopant, and the size of the nanorod in the polarizer will be more controllable.

[0097] 3. The reduction process in the stretching reduction preparation method involves the participation of reducing gas hydrogen in the reaction under high temperature and high pressure, which is dangerous. In addition, the overall reduction is not carried out in consideration of the economy and the scattering of metal particles during reduction. At this time, a sandwich structure is formed with two sides reduced and the middle unreduced. When the reduction thickness on both sides is inconsistent, stress is easily generated. The present application does not require a stretching reduction reaction, thus avoiding the danger of the reaction, and the metal-containing dopants in the entire composite matrix are stretched synchronously, which can make the overall preparation of the polarizer more controllable and more uniform, thus avoiding the generation of stress in the prior art.

[0098] 4. There have been reports of stretching reduction technology, which reduces the silver halide to silver particles, shrinks the volume, and the glass substrate has microscopic holes, which may affect the long-term reliability. In this application, there is no need to perform a reduction reaction after stretching, which greatly improves the long-term reliability of polarizer preparation and use.

[0099] 5. The working bandwidth of the sample with high extinction ratio prepared by stretching reduction method is limited, and the single-chip bandwidth reported so far is about 380nm. In this application, by controlling the size of the metal dopant, its size is controlled within a relatively wide range, which can help to broaden and regulate the working bandwidth of the polarizer.

[0100] It should be understood that expressions such as "including" and "may include" that may be used in the present application indicate the existence of the disclosed functions, operations, or constituent elements, and do not limit one or more additional functions, operations, and constituent elements. In the present application, terms such as "including" and / or "having" may be interpreted as indicating specific characteristics, numbers, operations, constituent elements, components, or combinations thereof, but may not be interpreted as excluding the existence or possibility of adding one or more other characteristics, numbers, operations, constituent elements, components, or combinations thereof.

[0101] In addition, in the present application, the expression "and / or" includes any and all combinations of the associated listed words. For example, the expression "A and / or B" may include A, may include B, or may include both A and B.

[0102] In the description of the embodiments of the present application, it should be noted that, unless otherwise clearly specified and limited, the term "connection" should be understood in a broad sense. For example, "connection" can be a detachable connection or a non-detachable connection; it can be a direct connection or an indirect connection through an intermediate medium. Among them, "fixed connection" means that the relative position relationship after connection remains unchanged. "Rotational connection" means that the two are connected to each other and can rotate relative to each other after connection. "Sliding connection" means that the two are connected to each other and can slide relative to each other after connection. The directional terms mentioned in the embodiments of the present application, such as "top", "bottom", "inside", "outside", "left", "right", etc., are only reference directions of the accompanying drawings. Therefore, the directional terms used are for better and clearer explanation and understanding of the embodiments of the present application, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the embodiments of the present application.

[0103] In addition, in the embodiments of the present application, the mathematical concepts mentioned are symmetry, equality, parallelism, verticality, etc. These limitations are all for the current state of the art, rather than being absolutely strict definitions in a mathematical sense, and allow a small amount of deviation, approximation to symmetry, approximation to equality, approximation to parallelism, approximation to verticality, etc. are all possible. For example, A and B are parallel, which means that A and B are parallel or approximately parallel, and the angle between A and B can be between 0 and 10 degrees. A and B are perpendicular, which means that A and B are perpendicular or approximately perpendicular, and the angle between A and B can be between 80 and 100 degrees.

[0104] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A polarizer composite base material, characterized in that: include: Base materials and metal-containing dopants; The metal-containing dopant is dispersed in the substrate; The metal-containing dopant comprises at least one of a metal rod, a metal-containing composite rod, a metal ball or a metal particle; the metal-containing composite rod comprises a sub-metal rod; The substrate is a stretchable material, and the materials of the substrate and the metal dopant are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range in which it can be stretched, the metal material in the metal dopant is in a semi-molten or molten state.

2. The composite base material according to claim 1, characterized in that: The weight proportion of the metal material in the metal-containing dopant in the composite base material is less than 20%; preferably, the weight proportion ranges from 0.05% to 10%.

3. The composite base material according to claim 1, characterized in that: The diameter range of the metal rod is A 10 -5 mm~A 10 -1 mm; preferably, the diameter range of the metal rod is A 10 -3 mm~A 10 -2 mm, A is the value of the thickness or diameter of the substrate, and the unit of the value is mm; The diameter range of the sub-metal rod is A 10 -4 mm~A 10 1 mm; preferably, the diameter range of the sub-metal rod is A 10 -2 mm~A 10 -1 mm; The metal ball is a nano metal ball; preferably, the diameter of the nano metal ball ranges from 5 nm to 500 nm; The metal particles are nano metal particles.

4. The composite base material according to claim 1, characterized in that: The metal balls are dispersed on the substrate in the form of single metal balls and / or metal ball assemblies; The metal particles are dispersed in the substrate in the form of a single metal particle and / or a combination of multiple metal particles.

5. The composite base material according to claim 1, characterized in that: A plurality of through holes are arranged in the substrate, and at least one metal-containing dopant is placed in one through hole; and / or the sizes of the metal-containing dopants in the substrate are the same or not completely the same; and / or the aspect ratio of the metal rod is greater than or equal to 1.5; preferably, the aspect ratio ranges from 2 to 100; the aspect ratio of the sub-metal rod is greater than or equal to 1.5; preferably, the aspect ratio ranges from 2 to 100.

6. The composite base material according to claim 1, characterized in that: The metal-containing composite rod comprises: at least one group of composite structures nested in each other; each group of composite structures comprises a plurality of sub-metal rods and a preset substrate wrapping the sub-metal rods; preferably, a core rod is arranged in the middle of the innermost composite structure; the material of the preset substrate and the core rod is the same as that of the substrate; further preferably, the material of the substrate is glass; or, the metal-containing composite rod comprises: a core rod and a plurality of sub-metal rods embedded in the core rod, the material of the core rod is the same as that of the substrate; further preferably, the material of the substrate is glass; and / or the mass proportion of the sub-metal rod in the metal-containing composite rod is less than 50%; And / or the softening point range of the substrate is 600°C to 1500°C.

7. A polarizing plate, characterized in that: The polarizer is obtained by stretching the composite matrix according to any one of claims 1 to 6; when the composite matrix is ​​stretched, the viscosity of the substrate is within the viscosity range in which it can be stretched, and the metal material in the metal dopant is in a semi-molten or molten state.

8. A method for stretching the polarizer according to claim 7, characterized in that: When the composite matrix is ​​stretched, the viscosity of the matrix is ​​controlled within a range of 10 2 mooring~10 13 Poise, preferably the substrate viscosity is 10 4 mooring~10 10 The tension is controlled within the range of 10MPa~300MPa, and the discharge speed is controlled within the range of 10mm / min~1000mm / min.

9. A method for preparing the polarizer composite base material according to any one of claims 1 to 6, characterized in that: include: Providing a substrate; Providing a metal-containing dopant; the metal-containing dopant comprises at least one of a metal rod, a metal-containing composite rod, a metal ball or a metal particle; the metal-containing composite rod comprises a sub-metal rod; The metal dopant is placed in a substrate to obtain a composite mother material; the substrate is a stretchable material, and the materials of the substrate and the metal dopant are selected to meet the following conditions: when the viscosity of the substrate is within the viscosity range in which it can be stretched, the metal material in the metal dopant is in a semi-molten or molten state.

10. The preparation method according to claim 9, characterized in that: When the metal-containing dopant is a metal rod or a metal-containing composite rod, the insertion is performed by punching; preferably, the metal-containing composite rod is inserted into the substrate by punching after being stretched; further preferably, when the insertion is performed by punching, holes are punched inside the substrate along the stretching direction of the substrate; When the metal dopant is a metal ball or metal particle, the implantation is performed by implantation; when the implantation is performed by ion beam implantation, the target material is at least one of silver, gold and copper, and the implantation is performed on both sides in the whole surface or in a regional selective manner, the implantation energy is greater than or equal to 10 MeV, and the gas pressure range during the implantation is 0.01 Pa to 1 Pa; preferably, the implantation area range of the regional selective implantation is 0.01 mm 2 ~10mm 2 The injection area interval range is 0.01Amm~5Amm, A is the numerical value of the thickness or diameter of the substrate, and the unit of the numerical value is mm; further preferably, when the injection method is ion beam injection, the thickness or diameter of the substrate is preferably 0.01mm~5mm.

Citation Information

Patent Citations

  • Polarized glass stretching equipment

    CN115724579A

  • Production of polarizer and apparatus for production

    JP1995301710A

  • Polarizing element and its production

    JP1997043429A

  • Polarizer and its production

    JP1997178939A

  • Polarizing element

    JP1997292517A